2021
DOI: 10.1111/imj.15084
|View full text |Cite
|
Sign up to set email alerts
|

Care to the end: a retrospective observational study of aged care facility residents transferred to hospital in the last day of life

Abstract: Background While transfer of aged care facility (ACF) residents to an acute hospital is sometimes necessary, for those at end of life this can cause fragmented care and disruption. Aim To explore the characteristics of ACF residents transferred to hospital in the last 24 h of life and factors that might influence this decision, including access to medical review, advance care planning (ACP) and pre‐emptive symptom management prescribing, an area not previously researched. Methods A retrospective observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Palliative care guidelines recommended that patient's preferences, medical decisions and treatment limitations should be included in the end‐of‐life care documents (Olsson et al, 2021). Earlier studies have shown, however, that ACP records were rare at the end‐of‐life stage (Brownstein et al, 2021; Izumi et al, 2020; Kuusisto et al, 2022; Sjöberg et al, 2021) and there was a lack of prognostication documentation, such as updating the patient's prognosis in the care plans (Gott et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Palliative care guidelines recommended that patient's preferences, medical decisions and treatment limitations should be included in the end‐of‐life care documents (Olsson et al, 2021). Earlier studies have shown, however, that ACP records were rare at the end‐of‐life stage (Brownstein et al, 2021; Izumi et al, 2020; Kuusisto et al, 2022; Sjöberg et al, 2021) and there was a lack of prognostication documentation, such as updating the patient's prognosis in the care plans (Gott et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Gott et al (2011), patients and family members were unaware of the care plan. In the case of palliative patients, it is especially important to take into account patients' own up‐to‐date wishes (Brownstein et al, 2021; Kuusisto et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of the Internal Medicine Journal , Brownstein and colleagues examine some of the characteristics of healthcare provision at the interface of RACF and State‐run healthcare facilities 8 . They examined the course of 149 older frail people who were transferred to hospitals and died there within 24 h. In general, most of the residents presented with an acute and distressing change in their condition and the transfer to acute care was mostly in keeping with their advance care plans, if available.…”
mentioning
confidence: 99%